2008
DOI: 10.1016/j.ejheart.2008.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized proteins in plasma of patients with heart failure: Role in endothelial damage

Abstract: Background: Oxidative stress is increased in the failing heart, and this might contribute to the pathogenesis of myocardial remodelling and heart failure (HF). Aim: To identify the oxidized proteins in plasma of chronic HF patients and to evaluate their possible role in endothelial damage. Methods: Plasma levels of oxidized proteins were measured by immunoassay and by analysis in albumin and immunoglobulin depleted plasma using a proteomic approach, in 40 HF patients and in 20 age-matched normal subjects. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 33 publications
1
38
1
6
Order By: Relevance
“…In addition, their chemical stability makes them suitable for laboratory measurement (Griffiths, 2000). The detection of high levels of protein carbonyls is a sign of oxidative stress and protein dysfunction (Dalle-Donne et al, 2003;Banfi et al, 2008), but we cannot exclude the possibility that other types of oxidative modification occur in salt-loaded and vehicle-treated SHRSPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, their chemical stability makes them suitable for laboratory measurement (Griffiths, 2000). The detection of high levels of protein carbonyls is a sign of oxidative stress and protein dysfunction (Dalle-Donne et al, 2003;Banfi et al, 2008), but we cannot exclude the possibility that other types of oxidative modification occur in salt-loaded and vehicle-treated SHRSPs.…”
Section: Discussionmentioning
confidence: 99%
“…Protein carbonyls were measured in the plasma samples and brain homogenates of animals sacrificed after 6 weeks of dietary treatment (Banfi et al, 2008) by using a Zentech PC test ELISA in accordance with the manufacturer's instructions (Biocell, Papatoetoe, Auckland, New Zealand). The plasma was collected in a citrate solution (0.129 M) and prepared by centrifugation at 1500g for 10 min at 4°C.…”
Section: Ppar-␣ Agonism Prevents Brain and Renal Damage In Shrspmentioning
confidence: 99%
“…It is now recognized that oxidation of proteins plays an essential role in the pathogenesis of an important number of degenerative diseases. Compared to controls more oxidized proteins are found in tissues from animals and patients suffering from Alzheimer's disease, rheumatoid arthritis, atherosclerosis or amyotrophic lateral sclerosis (Banfi et al, 2008). For example, in plasma from patients with Alzheimer`s disease the most obviously oxidized proteins were identified as isoforms of AAT and fibrinogen -chain precursor proteins.…”
Section: Oxidized and Nitrosylated Forms Of Appsmentioning
confidence: 98%
“…They also found that oxyA1AT might be an independent predictor of protein-energy wasting in patients on hemodialysis. Oxidized A1AT was also detected in patients with Alzheimer's disease, heart failure, and in premature rupture of the fetal membrane (Choi et al, 2002;Banfi et al, 2008;Izumi-Yoneda et al, 2009). …”
Section: Oxidation Of A1at -Clinical Aspectsmentioning
confidence: 99%